Philippines government directory. (Manila Diplomatic Post, 1989)
A directory of the Philippine government, from the Office of the President down to the municipal branches. It also has contact details for the Legislature and bureaucratic functions of the government, as well as income classification and code of conduct and ethics for public employees.
Title from cover.
Keywords: Administrative agencies -- Philippines -- Directories